Cooked Air - Elizabeth Galvez (Footprint)
Since 1996, ASHRAE Standard 62.2 has provided guidelines for residential ventilation. As ventilation becomes increasingly scientised, quantifiable, and reliant on hyper-specific equipment, technical literacy on ventilation has narrowed. The relationship between architecture, inhabitants and air management has become increasingly reliant on ventilation standards, in turn increasing reliance on technical specialists, and creating a gap in ventilation knowledge. Through an examination of ASHRAE Standard 62.2, this essay asks why is it that, as ventilation processes become increasingly measurable, there is an equal tendency to reverse awareness in relation to the human sensation, when the standard itself underlines the reality of both phenomenal and intellectual knowledge towards air quality assessment. Furthermore, if architecture’s domain centres on formal, aesthetic, and material logics, is an expanded literacy on air management necessary to address mechanical equipment within an architectural domain?